Microfluidic-Mass Spectrometry Interfaces for Translational Proteomics. Issue 10 (October 2017) - Pedde, R. Daniel; Li, Huiyan; Borchers, Christoph H.; Akbari, Mohsen
Abstract : Interfacing mass spectrometry (MS) with microfluidic chips (μchip-MS) holds considerable potential to transform a clinician's toolbox, providing translatable methods for the early detection, diagnosis, monitoring, and treatment of noncommunicable diseases by streamlining and integrating laborious sample preparation workflows on high-throughput, user-friendly platforms. Overcoming the limitations of competitive immunoassays − currently the gold standard in clinical proteomics − μchip-MS can provide unprecedented access to complex proteomic assays having high sensitivity and specificity, but without the labor, costs, and complexities associated with conventional MS sample processing. This review surveys recent μchip-MS systems for clinical applications and examines their emerging role in streamlining the development and translation of MS-based proteomic assays by alleviating many of the challenges that currently inhibit widespread clinical adoption. Trends: Interfacing microfluidics with mass spectrometry (μchip-MS) provides attractive solutions to overcome the limitations of competitive immunoassays (the current gold standard) and conventional mass spectrometery-based approaches. The automation and integration of complex sample processing protocols, enabled by μchip-MS, hold considerable promise to streamline clinical mass spectrometry-based workflows on user-friendly platforms. μChip-MS could accelerate the development of rapid, high-throughput bioanalytical workflows and serve a pioneering role in their clinical translation.